A global analysis of enemy release and its variation with latitude. Issue 1 (23rd November 2020) - Xu, Meng; Mu, Xidong; Zhang, Shuang; Dick, Jaimie T. A.; Zhu, Bingtao; Gu, Dangen; Yang, Yexin; Luo, Du; Hu, Yinchang
Abstract: Aim: The enemy release hypothesis (ERH) posits that exotic species suffer less enemy damage than natives, which promotes their successful invasion. However, the generality of less damage for exotics remains widely debated. A recent view proposes that enemy release (ER) could change systematically with latitude, potentially helping to explain these inconsistencies. Here, we test whether exotic plant species suffer consistently lower herbivore damage relative to natives and whether ER varies with latitude. Location: Global. Time period: 1960–2018. Major taxa studied: Plants. Methods: Using leaf herbivory data for 1, 098 plant species, we compared the herbivory rate between exotic and native plants across all taxa, between the introduced and native range of exotic species and between exotic and native species co‐occurring in the same community. We tested the interaction effect between origin (exotic versus native) and latitude to assess variation in ER with latitude. We also examined whether the effect of origin and its interaction with latitude changed with plant growth form (woody versus non‐woody). Finally, based on two ER effect‐size datasets, two meta‐regressions were performed to demonstrate the relationship between ER and latitude. Results: Leaf herbivory rates were commonly lower for exotics than for natives. However, this differential herbivory rate was significant only for woody plants. No significant interactions were found between origin and latitude, indicating that ER did not change with latitude. The meta‐regressions also demonstrated that ER was not significantly correlated with latitude. Main conclusions: The widespread lower herbivory rate for exotic compared with native woody plant species supports the ERH for exotic woody plants. Consistent ER with latitude indicates that ER should play a similar role regardless of latitude. One future challenge is to assess the extent to which ER in woody exotic plants translates to performance advantages and thereby influences their invasion success.